Studi Living Hadis: Implementasi Moderasi Beragama di Tengah Masyarakat Muslim Kudus - Emiliana, Eka; Kusumaningtyas, Amelia Titik; Kurniawan, Muhammad Arif (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2024)
This article aims to describe the implementation of religious moderation in Tanjung Karang Village, which consists of various religions, ranging from Islam, Christianity, Confucianism and Buddhism. In order to avoid conflict between communities, it is necessary to realize the principle of religious moderation. Religious moderation is a concept that emphasizes mutual respect and tolerance among different religious groups. This is as stated by the Prophet Muhammad Saw in a hadith about